Neuropsychiatric Symptoms in Patients with the Main Etiological Types of Mild Neurocognitive Disorders: A Hospital-Based Case–Control Study - Oleg A. Levada; Nataliya V. Cherednichenko; Alexandra S. Troyan (Frontiers in Psychiatry, 2017)
BackgroundThe diagnostic construct of mild neurocognitive disorders (MNCDs) is substantially congruent with previously proposed criteria for mild cognitive impairment (MCI). MNCD/MCI is associated with neuropsychiatric symptoms (NPS). Previous studies have examined the prevalence of NPS in amnestic and non-amnestic MCI subtypes; however, no studies exist for etiological types of MNCD. We aimed to estimate the prevalence of NPS in patients with MNCD due to Alzheimer’s disease (MNCD-AD) and subcortical vascular MNCD (ScVMNCD) and to determine whether NPS would expand these MNCD phenotypes.MethodsThe sample comprised 70 patients with MNCD-AD, 70 patients with ScVMNCD, and 55 cognitively normal elderly persons (CNEP). The diagnosis of MNCD-AD was made according to DSM-5 criteria for possible MNCD-AD. ScVMNCD patients fulfilled the DSM-5 criteria of the probable vascular MNCD and the diagnostic criteria for subcortical vascular MCI according to Frisoni et al. (1). The prevalence of NPS was based on the neuropsychiatric inventory. The statistical analyses included parametric and non-parametric tests, multivariate regression, and Spearman’s correlation coefficient.ResultsAbout 69.1% of CNEP, 97.1% of MNCD-AD, and 100% of ScVMNCD patients had one or more NPS. The prevalence of NPS in both MNCD groups was significantly higher than that in CNEP. The most prevalent NPS that had significant differential diagnostic value in separating MNCD-AD from ScVMNCD, as well as MNCD from CNEP, were anxiety (81.43%) and irritability (67.14%) in MNCD-AD and depression (81.43%) in ScVMNCD. In both MNCD groups, we observed significant (p < 0.05) correlations between all distinguishing NPS and the differential cognitive disturbances: the amnestic syndrome in MNCD-AD and executive dysfunction in ScVMNCD.ConclusionNPS occur in the majority of persons with MNCD-AD and ScVMNCD. Anxiety and irritability are the most prevalent NPS in MNCD-AD, as well as depression in ScVMNCD. The amnestic–anxious–irritable syndrome can be the main phenotype in MNCD-AD, on the other hand, the dysexecutive–depressive syndrome can be considered as the most prevalent clinical manifestation in ScVMNCD. Obtained data may be used for clinical differentiation of MNCD-AD and ScVMNCD patients.